Los Viajes de Riva-Agüero - Wiesse Rebagliati, Jorge (2019)
Regarding José de la Riva-Agüero’s Viajes, some textual traits are pinpointed: the construction of a narrative persona, the description of landscapes and the ideal identity between Spanish Castille and the Peruvian Sierra. Similarities and differences between Viajes and Paisajes peruanos [Peruvian Landscapes], Riva-Agüero’s major travel book, are also discussed.